Answer:
A is your answer
Step-by-step explanation:
A
The solution (x,y) needs to work in both equations. With multiple choice you can do guess and test method. Otherwise you need to combine the two equations into one by substitution or elimination methods.
21. substitution works well here since one equation is y= x+3. you can easily substitute the (x+3) for y in the other equation.
2x + (x+3) = -6
3x + 3 = -6
3x = -9
x = -3
use this in either equation to find y.
y = (-3)+3
solution: (-3,0)
22. these both equal y so they equal each other.
4x - 1 = 3x +6
4x - 3x = 6 + 1
x = 7
use this in either equation to find y
y = 4(7) - 1
y = 28 - 1
y = 27
solution: (7,27)
23. one equation is y = 2x - 3. So substitute (2x -3) for y in the other equation.
4x = 2(2x - 3) + 6
4x = 4x - 6 + 6
4x = 4x
x = x
any solution will work, infinitely many.
24. infinitely many solutions means the two equations are the same equation. Like the previous one they didn't look the same but if you put them both in terms of y...
y= 2x-3
4x = 2y + 6
4x - 6 = 2y
(4x - 6)/2 = y
2x - 3 = y
same equation.
from the image, I can't see all options but A & C do not look like the same equations. It's got to be either B or D.
Answer:
a. $13
b. $3
Step-by-step explanation:
Juan wants to start a lemonade stand to earn money. He needs money to purchase the materials before he can sell the lemonade and earn money. His mother agrees to loan him $10. He makes a list of the items he wants to buy.
Cups $2
Lemons $8
Sugar $3
a. How much money do the supplies cost?
b. How much money does he have to spend?
a. Cost of each supply;
Cups $2
Lemons $8
Sugar $3
Total cost of the supplies = $2 + $8 + $3
= $13
b. How much money does he have to spend?
His mother agreed to loan him $10
Total cost of supplies = $13
Amount of money he has to spend = Total cost of supplies - Loan from his mother
= $13 - $10
= $3
82+2x=180
2x=98
x=49
answer is x=49
We have that
4x²-25y²<span>-8x+50y-121=0
</span><span>Group terms that contain the same variable, and move the constant to the opposite side of the equation
</span>(4x²-8x)+(-25y²+50y)=121
Factor the leading coefficient of each expression
4(x²-2x)-25(y²-2y)=121
Complete the square twice. Remember to balance the equation by adding the same constants to each side.
4(x²-2x+1)²-25(y²-2y+1)²=121+4-25
Rewrite as perfect squares
4(x-1)²-25(y-1)²=100
<span>Divide both sides by the constant term to place the equation in standard form</span>
(4/100)(x-1)²-(25/100)(y-1)²=100/100
(1/25)(x-1)²-(1/4)(y-1)²=1
[(x-1)²]/25-[(y-1)²]/4=1
the answer is
[(x-1)²]/25-[(y-1)²]/4=1